Development and quality evaluation of retort pouch packed tender jackfruit (Artocarpus heterophyllus L.) - PRAVEENA N; Dr. Sudheer K. P (Guide) (Tavanur 2015 Department of Food & Agricultural Process Engineering)
Development and quality evaluation of retort pouch packed tender jackfruit (Artocarpus heterophyllus L.)
Development and quality evaluation of retort pouch packed tender jackfruit (Artocarpus heterophyllus L.)